Staphylococcus aureus lipoproteins play crucial roles in inducing inflammatory responses and bacterial internalization into bovine mammary epithelial cells. (January 2022) - Liu, Bo; Li, Qianru; Gong, Zhiguo; Zhao, Jiamin; Gu, Baichen; Feng, Shuang
Abstract: Bovine mastitis is caused by bacterial infection and characterized by inflammatory and infectious processes. Staphylococcus aureus frequently causes subclinical mastitis in dairy cows. In this study, we aimed to investigate the roles of S. aureus lipoproteins in inducing inflammatory responses and in mediating bacterial internalization into bovine mammary epithelial cells (bMECs). The results showed that TLR2 expression in bMECs infected with S. aureus isogenic mutant deficient in lipoprotein maturation was decreased compared to that in bMECs infected with wild-type S. aureus . Lipoproteins from S. aureus and the engagement of TLR2 were essential for inducing the activation of MAPK and NF-κB signaling, and stimulating the secretion of the inflammatory mediators tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and C-X-C motif chemokine ligand 8 (CXCL8). The production of prostaglandin E2 (PGE2 ) and the expression of PTGS2 in S. aureus -infected bMECs were dependent on the presence of bacterial lipoproteins. Furthermore, bacterial lipoproteins contributed to S. aureus internalization into bMECs. These findings suggest the S. aureus lipoproteins are key immunobiologically active compounds that trigger inflammatory responses in bMECs and play an important role in S. aureus internalization into bMECs. Highlights: Lipoproteins play key roles in inducing TLR2 activation in S. aureus -infected bMECs. S. aureus lipoproteins are crucial for induction of inflammatory responses in bMECs. S. aureu s lipoproteins are required for S. aureu s internalization into bMECs.